Moduli and extremal metrics on nonorientable and twisted Riemannian manifolds - Tamrazov, P. M. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We present results on the moduli and extremal metrics of families of curves on certain nonorientable or twisted Riemannian manifolds. We also introduce and investigate weighted l-moduli of families of curves and the corresponding extremal metrics.